A Study to Examine the Effect of Needle Gauge on Pain Perception in Patients Receiving Treatment With Botulinum Toxin in 2 Different Anatomical Areas. Issue 4 (December 2020) - Hollingsworth, Karen E.; Brown, Tim
Abstract: Botulinum toxin injection for treatment of rhytids is the commonest cosmetic intervention undertaken worldwide. It requires re-treatment at 3-month intervals for the effect to remain. Consequently, patient comfort is paramount in order for the procedure to remain acceptable. Intuitively, patients expect that smaller needles will be less painful, and this study examines the pain caused by needles of 2 gauges (31 and 32) when administering botulinum toxin in 2 anatomical areas. Patients were randomized into having the left or right side of their face treated with either a 31- or 32-gauge needle during botulinum toxin administration. Participants were asked to determine whether the left- or right-side treatment was most painful. The study was repeated in the glabellar and paraorbital regions. A total of 103 participants entered the study; 98 had the glabellar region treated and 76 the crow's feet, and 72 patients had both regions treated. For the glabellar region, the smaller 32-gauge needle was significantly more painful than the larger 31-gauge needle ( P  < .01). There was no difference in patient's pain perception between gauges of needle when treating the crow's feet area ( P  = .9). The 31-gauge needles produce significantly less pain than smaller 32-gauge needles when treating the glabellar region with botulinum toxin, but not in the periorbital region. We propose that this is due to differences in fascial adherence between the 2 areas. Consequently, we would recommend administering botulinum toxin with a 31-gauge needle in all areas.